The effect of family empowerment through education and mentoring on increasing knowledge of exclusive breastfeeding - Kamsatun Kamsatun (PAGEPress Publications, 2023)
Providing appropriate education to breastfeeding mothers and their families is essential to ensure a high level of breastfeeding implementation. The purpose of this study was to analyze the effect of education and mentoring on increasing knowledge about exclusive breastfeeding. This study employed a quasi-experimental design with two groups, one before and one after testing. The research was conducted in one village during March and April 2023, using purposive sampling techniques. Data were collected through questionnaires. Family empowerment interventions in the form of education and mentoring were administered twice with one-week intervals. Data analysis was performed using an independent t-test with p-value < 0,05. The study revealed significant differences in respondents' knowledge after they received educational interventions and guidance. The results showed a p-value of 0.006, which is less than 0.05, indicating a significant difference in respondents' knowledge before and after the intervention. Education and instruction had a positive impact on respondents' knowledge of exclusive breastfeeding. Both the intervention and control groups showed efficacy. Notably, the intervention group displayed a highly significant increase, as evidenced by the significant difference values. In conclusion, family empowerment through education and assistance has a positive effect on increasing knowledge about exclusive breastfeeding. Enhancing family knowledge, skills, and social support can lead to improved optimal breastfeeding practices, enhanced infant health, and reduced infant mortality.